A Novel Orange-Red Emitting ZnB4O7:Eu3+ Phosphor with Urchin-Like Nanostructure - Hom Nath Luitel; Rumi Chand; Takanori Watari (Advances in Condensed Matter Physics)
A novel phosphor, ZnB4O7:Eu3+, with urchin-like structure consisting of radially arranged high density nanorods was successfully synthesized by hydrothermal process at 150°C for 24 h. The nanorods were measured from 200 to 400 nm in diameter and several µm in length. The urchins were few µm to 40 µm in diameter. The ZnB4O7:Eu3+ phosphors were efficiently excited by ultraviolet (UV ~ 254 nm) to visible light of ~ 220 to 450 nm and exhibited intense orange-red emission consisting of main peaks at 590, 615, and 695 nm due to the charge transfer in the host and f→f transitions (5D0 to 7F1,2,4) of the Eu3+ ions. Effect of the Eu3+ ions concentration on the photoluminescence (PL) emission intensity was investigated and it was found that 5 at% Eu3+ is the optimum concentration. Meanwhile, the concentration quenching mechanism was discussed. The key parameters, such as temperature dependent PL and CIE values of ZnB4O7:Eu3+ phosphors, were studied. The ZnB4O7:Eu3+ phosphor exhibited good thermal stability and better absorption cross section compared to the commercial Y2O2S:Eu3+ phosphor. All these characteristics indicate that the phosphor will be a potential candidate for the UV based white LEDs.